Hypo-excitation across all cortical laminae defines intermediate stages of cortical neuronal dysfunction in diffuse traumatic brain injury. (15th October 2016) - Allitt, Benjamin J.; Iva, Pippa; Yan, Edwin B.; Rajan, Ramesh
Highlights: A rodent model of traumatic brain injury (TBI) was used to assess cortical processing 2 weeks post-injury. Short-term suppression of neural firing rates had spread from supra to infragranular layers. TBI induced temporal abnormalities in neural coding and dysfunction in complex stimuli processing. Abstract: Traumatic brain injury (TBI) is a major cause of morbidity and mortality world-wide and can result in persistent cognitive, sensory and behavioral dysfunction. Understanding the time course of TBI-induced pathology is essential to effective treatment outcomes. We induced TBI in rats using an impact acceleration method and tested for sensorimotor skill and sensory sensitivity behaviors for two weeks to find persistently poor outcomes post-injury. At two weeks post-injury we made high resolution extracellular recordings from barrel cortex neurons, to simple and complex whisker deflections. We found that the supragranular suppression of neural firing (compared to normal) previously seen in the immediate post-TBI aftermath had spread to include suppression of input and infragranular layers at two weeks post-injury; thus, there was suppression of whisker-driven firing rates in all cortical layers to both stimulus types. Further, there were abnormalities in temporal response patterns such that in layers 3–5 there was a temporal broadening of response patterns in response to both whisker deflection stimulus types and in L2 a narrowing of temporal patterns in response to the complex stimulus. Thus, at two weeks post-TBI, supragranular hypo-excitation has evolved to include deep cortical layers likely as a function of progressive atrophy and neurodegeneration. These results are consistent with the hypothesis that TBI alters the delicate excitatory/inhibitory balance in cortex and likely contributes to temporal broadening of responses and restricts the ability to code for complex sensory stimuli.